PENGEMBANGAN MEDIA POP UP BOOK TERHADAP HASIL BELAJAR SISWA KELAS II SEKOLAH DASAR - Latifah, Nadlirotul; Galuh Kartika Dewi; Satrio Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by developing pop up book learning media to improve the learning outcomes of class II students at SDN Sidokepung 1 Sidoarjo in Pancasila education learning. The aim of this research is to find out whether the Pop Up Book media is suitable for use with second grade elementary school students and to find out the learning outcomes of second grade elementary school students after using pop up book media. This research uses the Research and development (R&D) development method which uses 7 procedures, namely potential and problems, data collection, product design, product validation, product revision, product testing, design revision. This research was conducted at SDN Sidokepung 1 Sidoarjo which consisted of 19 samples. The results of media validation produced 81% data categorized as "Feasible and Quite Effective", and the results of material validation produced 9.7% data or categorized as "Appropriate" for use. The results, students in the class at SDN Sidokepung 1 Sidoarjo produced effective learning results, namely 60.52 in the pretest and 86.84 in the posttest with an N-Gain value of 84.18. The results of the research are that the pop up book media is very suitable for use and improves learning outcomes for students II at SDN Sidokepung 1 Sidoarjo.